Perancangan Balanced Scorecard Sebagai Alat Penentuan Strategi : Studi Kasus Pada Sub Bagian Non PNPB Universitas Palangka Raya - Medianson Medianson; Danes Jaya Negara; Fitria Husnatarina; Lelo Sintani; Meitiana Meitiana; Luluk Tri Harinie (FKIP, Universitas Palangka Raya, 2023)
This study aims to analyze the main strategies that must be developed, analyze strategic objectives, analyze performance measures and recommend managerial implications of the Non-Tax State Budget Subdivision of the Finance Department of the University of Palangka Raya based on the Balance Scorecard perspective. The results of environmental analysis using descriptive analysis, evaluation of internal factors, evaluation of external factors, and the internal-external matrix selected an intensive product development strategy as the main strategy for the Non PNPB Subdivision of the University of Palangka Raya. The results of the research at a later stage note that the customer perspective (0.573) is the most important perspective of the four Balanced Scorecard perspectives in product development strategy, while the strategic objective of